Fatores associados à qualidade de vida de idosos hospitalizados - Bruna Martins; Aparecida Yosie Yoshitome; Thais Fernanda Vieira; Danila Cristina Paquier Sala; Gerson Scherrer Júnior; Meiry Fernanda Pinto Okuno (Universidade Federal de Santa Maria, 2021)
Objective: to evaluate the quality of life of hospitalized elderly people and their association with sociodemographic, economic, length of stay and having a caregiver variables. Method: cross-sectional study, in which one hundred participants were included. Data collection took place between September 2018 and April 2019. The 36-Item Short Form Health Survey was applied. Spearman and Mann-Whitney correlation coefficient statistical tests were used. Results: mental health and physical aspects were, respectively, the domains of quality of life with the highest and lowest scores. Male, employed, without a caregiver, older age and family income were positively associated with quality of life; and negatively longer hospitalization and having a caregiver. Conclusion: the variables associated with quality of life were sex, age, occupation, higher family income, length of stay and caregiver. Care for hospitalized elderly should be planned, taking into account factors that interfere with quality of life.